The effects of owning a pet on self-esteem and self-efficacy of Malaysian per owners - Cheong, Sau Kuan *; Teoh, Hsien-Jin *; Ng, Alvin Lai Oon * (Sunway University College, 2005)
In this research, 200 pet owners and non-pet owners were studied to ascertain the effects of owning a pet on the self-esteem and self-efficacy of the pet owners. All the respondents completed self-reported questionnaires. While the results showed no significant differences, it was noted that there was a tendency for people with pets to generally have slightly higher self-esteem and self-efficacy as compared to people without pets. The study also showed that higher self-esteem contributed towards predicting higher self-efficacy.